2005
DOI: 10.1021/ic051859q
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-Atom Exchange Mediated by Nitrido Complexes of Molybdenum

Abstract: Nitrido complexes NMo(OC(CF3)2Me)3 and NMo(OC(CF3)3)3(NCMe) containing fluorinated alkoxide ancillary ligands are synthesized in 57% and 50% yield, respectively. Both complexes undergo N-atom exchange within hours at 30 degrees C with acetonitrile and benzonitrile in either THF-d8 or CD2Cl2, as shown by 15N NMR studies using labeled 15NCMe. In both solvents, is the more active in this process. Additionally, both compounds are substantially more active in THF-d8 than in CD2Cl2. Complex crystallizes in the space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 19 publications
0
31
1
1
Order By: Relevance
“…[16] Johnson found that although in the case of trialkoxytungsten(VI) complex 35, the formation of nitride 36 from alkylidyne 35 and nitrile is favored, [48][49][50] the molybdenum(VI) analogue showed thermodynamic preference for the formation of alkylidyne complex from nitride species and alkynes (Scheme 8). Although no terminal nitrido com-plexes were formed in the reaction between propylidyne complex 38 and nitriles, heating nitride 37 [51] with 3-hexyne and 1 equiv. of DME at 95 8C for several days generated compound 38.…”
Section: Molybdenum-based Catalyst Prepared From Nitrides By Metathesmentioning
confidence: 99%
“…[16] Johnson found that although in the case of trialkoxytungsten(VI) complex 35, the formation of nitride 36 from alkylidyne 35 and nitrile is favored, [48][49][50] the molybdenum(VI) analogue showed thermodynamic preference for the formation of alkylidyne complex from nitride species and alkynes (Scheme 8). Although no terminal nitrido com-plexes were formed in the reaction between propylidyne complex 38 and nitriles, heating nitride 37 [51] with 3-hexyne and 1 equiv. of DME at 95 8C for several days generated compound 38.…”
Section: Molybdenum-based Catalyst Prepared From Nitrides By Metathesmentioning
confidence: 99%
“…Fürstner et al [18,19] utilize Br 3 WhCPh(dme) [20,21] as an accessible reagent to form siloxy-based alkylidyne complexes [22]. For example, (Ph 3 SiO) 3 MohCPh(OEt 2 ) reacts with many substrates bearing diverse functional groups, and the activity is impressive [23]. In the presence of 5 Å molecular sieves, (Ph 3 SiO) 3 MohCPh(OEt 2 ) completes the metathesis of 1-phenyl-1-propyne within 5 min.…”
Section: Introductionmentioning
confidence: 99%
“…Moore [17], employing the Lewis acid B(C 6 F 5 ) 3 , activate Mo-nitrides toward metathesis with alkynes. This discovery implies that Mnitrides, already known to exchange N-atoms with nitriles [23,24], may be a general entry point to alkyne metathesis catalysts [15,16]. Recently, we proposed that a trianionic pincer ligand may provide the appropriate ligand arrangement for a reactive AM or NACM catalyst [25].…”
Section: Introductionmentioning
confidence: 99%
“…Bis(4-methoxyphenyl)acetylene [24,25], VCl 3 (thf) 3 [26], N^Mo(OCMe 3 ) 3 (6) [27], N^Mo(OCMe(CF 3 ) 2 ) 3 (1) [28], and N^Mo(OC(CF 3 ) 3 ) 3 (NCMe) (2) [28], were prepared according to literature procedures. Mesitylene, diphenylacetylene, and chlorotitanium tri-isopropoxide were obtained from Acros.…”
Section: Methodsmentioning
confidence: 99%